Smart Helmet System For Advanced Safety Using Iot - Reddy, Munagala Navadeep; Reddy, Poli Sainath; Kumar, Shaik Suraj; Shankar, Tanga Siva; Ananth, S.; Nithiya, M. (Journal of Neonatal Surgery, 2025)
By consolidating many real-time monitoring capabilities into a single, affordable unit, the suggested smart helmet system is an Internet of Things (IoT) based safety solution that aims to improve the protection of riders of two-wheelers. Based on an Arduino Uno microcontroller, the system makes use of an infrared sensor to identify when a helmet has been worn, a multi-gas meter to measure blood alcohol content, and an accelerometer to identify when an accident has occurred. The device utilizes a relay module to disable vehicle ignition in the event that the helmet is not worn or if alcohol is detected. The system has a GPS module that automatically tracks the rider's position in case of an accident and a GSM module that notifies pre-set contacts of the rider's whereabouts. This smart helmet is a small, practical, and energy-efficient way to reduce road fatalities and improve emergency response times. It uses both proactive and reactive techniques to keep riders safe